A quasi-static model for hot-electron interaction with self-generated magnetic fields. (9th April 2019) - Curcio, A; Volpe, L
Abstract: The time evolution of the target temperature and ionization degree during the laser-target interaction is of primary importance to understanding the transition between solid and plasma. When the interaction lasts a few tens of femtoseconds, the target resistivity is not well known as in the Spitzer regime, and therefore approximated information must be used from experiments and/or from models. The calculation of the target temperature and the magnetic fields produced inside the target after the propagation of a fast electron current is performed in this paper accounting for the pulse temporal envelope and making use of a complete resistivity model. Analytic calculations of temporal and spatial varying magnetic fields are also presented. Finally, a novel interpretation of the beam hollowing phenomenon is given based on the outcomes of the model developed.